PATHOPHYSIOLOGICAL MECHANISMS OF DEHISCENCE OF ANASTOMOSE SUTURES IN PATIENTS WITH ONCOPATHOLOGY - O.V. Movchan; A.V. Titkova (Проблеми екології та медицини, 2018)
It should be recognized that the creation of optimal conditions for healing of intestinal sutures is the main reserve for improving the results of surgical intervention on the organs of the gastrointestinal tract. The urgent issues of pathophysiology associated with oncopathology remain the inability of seams of anastomosis and stomaty. The purpose of the work is to determine the pathophysiological mechanisms and criterion-significant indicators of inability to sew anastomosis. In the study of this issue, an analysis of the immediate results of treatment of 74 patients, which was a test group, which operative treatment was performed in a radical volume. Patients were divided into two groups according to the anastomosis failure: Group Іa - patients who had been operated on for gastric cancer and who had anastomosis failure - 16 patients, II group 58 patients - who had been surgically inoperative and had not been diagnosed insolvency The patients of each group were divided into four subgroups, depending on the presence of instability of microsatellites in the locuses of the VAT-25, VAT-26. The presence of Streptococcus Bovis stomach cancer patients may be an early marker of disease progression. The leading metabolic profile of microbiocenosis in the development of stomach cancer is the significant accumulation of biogenic amines. The analysis of the results of the study shows that the failure of anastomosis in patients with gastric cancer is accompanied by profound disorders of the metabolism of connective tissue and is confirmed by increased activity of elastase, collagenolithic activity of blood serum and its content of glycosaminoglycans. The activity of elastase and glycosaminoglycans may be a prognostic criterion for insufficiency of seams in the course of treatment.